The role of inflammation in diabetic cardiomyopathy - Reis, Flávio (2012)
Type 2 diabetes mellitus (T2DM) is a major risk factor for developing cardiovascular disease and represents a serious public health problem, with high rates of mortality and morbidity worldwide. T2DM etiology is complex and multifactorial and is associated with several complications, including those at myocardium level. Diabetic cardiomyopathy (DCM) is viewed as a specific cardiomyopathy and defined as structural and functional changes in the myocardium due to metabolic and cellular abnormalities induced by diabetes. T2DM has long been classified as an inflammatory disease and recent studies have identified the importance of the inflammatory process in the development and progression of heart failure. In this review, the authors outline the main mechanisms underlying the potential contribution of the inflammatory process in the development and evolution of DCM. In addition, potential therapeutic strategies against inflammation of DCM are discussed.